First evidence of stone handling in geladas: From simple to more complex forms of object play - Cangiano, Maria; Palagi, Elisabetta (Behavioural processes, 2020)
•Our study reveals the presence of stone handling (SH) outside the Macaca genus.•Geladas are a derived species of Papionini representing a good model to test hypotheses on SH.•SH in geladas peak when they are juveniles and persists into adulthood.•SH behaviour increases in complexity along with the age of the player.•SH does not seem to be a misdirected foraging activity. Stone Handling (SH) is a solitary object play behaviour that can vary from simple exploratory actions to more complex manipulations. So far, among primates, this behaviour has been exclusively reported in macaques. We collected data on 62 geladas (Theropithecus gelada) housed at the NaturZoo (Rheine, Germany). We found that about 70% of subjects belonging to all age- and sex-classes engaged in SH. Due to their exceptional manipulative skills (the highest opposability index among nonhuman primates) and propensity to play, geladas are a good model species to test hypotheses on the function of this form of object play. While the frequency of SH tended to decrease with age of the player, the duration of each session and its complexity tended to increase in juveniles/subadults and adults compared to infants. This age-related variation in terms of frequency, duration and complexity suggests that, in agreement with the motor training hypothesis, SH could have a role in the neural–motor development of immature subjects and a basic function in stimulating neurogenesis and maintaining the psychological well-being of adults. In all age classes, the frequency of SH did not vary across pre-feeding, feeding and non-feeding conditions. Hence, our data do not support the misdirected foraging hypothesis, which predicts that animals engage in SH to anticipate food provisioning. In conclusion, our study reveals, for the first time, the presence of SH outside the genus Macaca and attempts to delineate possible functions of the behaviour in geladas. Since the hypotheses tested cannot be mutually exclusive, long-term studies of SH across individuals’ lifetimes in both captive and wild groups of geladas are needed to clarify the proximate and ultimate functions of the behaviour in this species of Papionini. Finally, long-term studies could also provide some important indications about the cultural nature and social transmission of SH in a taxonomic group outside the Macaca genus.